Exploring the relationship between psychological capital, emotional intelligence, psychological safety, and knowledge sharing among E-commerce practitioners - Zhang, Xuan; Xu, Ziqing (Frontiers in Psychology, 2024)
Introduction: This study explores the intricate relationships among psychological capital, emotional intelligence, psychological safety, and knowledge sharing among e-commerce practitioners. Grounded in social exchange theory, the research aims to fill a gap in the literature by focusing on the psychological and emotional factors influencing knowledge sharing in a fast-paced and highly competitive industry. Methods: This study used snowball and purposive sampling to collect 439 valid online questionnaires from e-commerce professionals in Guangdong, Zhejiang, and Jiangsu, China. The survey, conducted from October to November 2023, explored the relationships between psychological capital, emotional intelligence, psychological safety, and knowledge sharing. Data were analyzed using structural equation modeling (SEM) with AMOS 26.0. Results: The structural path model revealed significant positive correlations between psychological capital and both emotional intelligence (β = 0.494, p < 0.001) and psychological safety (β = 0.297, p < 0.001). Emotional intelligence was significantly positively related to psychological safety (β = 0.513, p < 0.001) and knowledge sharing (β = 0.452, p < 0.001). Psychological safety was also positively correlated with knowledge sharing (β = 0.311, p < 0.001). Bootstrap analysis indicated that emotional intelligence and psychological safety significantly mediate the relationship between psychological capital and knowledge sharing (standardized indirect effect = 0.394, p < 0.01). Discussion: Based on the significant findings of this study, a key recommendation is to implement targeted interventions aimed at enhancing psychological capital, emotional intelligence, and psychological safety among e-commerce practitioners. Specifically, developing training programs focused on building resilience, self-efficacy, hope, and optimism can improve employees’ psychological capital. Additionally, workshops designed to enhance emotional intelligence and create a culture of psychological safety can encourage open communication and trust, thereby promoting knowledge sharing.